2021
DOI: 10.1158/2326-6066.cir-21-0846
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal lncRNA-Mediated Intercellular Communication Promotes Glioblastoma Chemoresistance

Abstract: Standard treatment for glioblastoma (GBM) is surgery followed by radiotherapy and chemotherapy, often with the chemotherapeutic agent temozolomide. However, this treatment is not curative. In this issue, Li and colleagues uncover a novel circuit regulating GBM cell resistance to temozolomide that involves exosome-mediated transfer of the long noncoding RNA (lncRNA) lnc-TALC (temozolomide-associated lncRNA in glioblastoma recurrence) to microglial cells. The results provide new targets for therapeutics that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…LncRNAs act intracellularly and may also be secreted by adipocytes and transported via the 835 bloodstream to other cells or tissues, where they are considered to be circulating lncRNAs [246]. 836 Therefore, they may contribute to intercellular communication as autocrine, endocrine, or paracrine 837 molecules [246,247], although the exact process of lncRNA release into the extracellular environment 838 is unknown. 839…”
Section: Lncrnas As Biomarkers 832mentioning
confidence: 99%
“…LncRNAs act intracellularly and may also be secreted by adipocytes and transported via the 835 bloodstream to other cells or tissues, where they are considered to be circulating lncRNAs [246]. 836 Therefore, they may contribute to intercellular communication as autocrine, endocrine, or paracrine 837 molecules [246,247], although the exact process of lncRNA release into the extracellular environment 838 is unknown. 839…”
Section: Lncrnas As Biomarkers 832mentioning
confidence: 99%
“…A number of lncRNAs have high tissue expression specificity and are evolutionary conserved (12). Previous pan-cancer transcriptome analysis showed that the expression of lncRNAs were frequently dysregulated and in manner that was specific to multitude of tumors, including lung cancer (13), breast cancer (14), and glioblastoma (8,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%